Practical data migration - Morris, Johny (BCS, The Chartered Institute for IT, 2020)
This book is for executives, practitioners, and project managers who are tasked with the movement of data from old systems to a new repository. It is designed as a practical guide and uses a series of steps developed in real-life situations that will get you from an empty new system to one that is populated, working and backed by the user population. This new edition is updated to take account of changes in technology and the maturing of the market for data migration services, with two brand new chapters. It guarantees to get the dirty old data out of your legacy systems and transform it into clean new data for your new system.
Includes index.
Keywords: Database management.; Electronic data processing.; elektronické knihy; electronic books